2022
DOI: 10.1111/ijd.16063
|View full text |Cite
|
Sign up to set email alerts
|

SARS‐CoV‐2 vaccine‐related cutaneous manifestations: a systematic review

Abstract: To date, over 250 million people have been reportedly infected by COVID‐19 disease, which has spread across the globe and led to approximately 5.1 million fatalities. To prevent both COVID‐19 and viral transmission, DNA‐based/RNA‐based vaccines, non‐replicating viral vector vaccines, and inactivated vaccines have been recently developed. However, a precise clinical and histological characterization of SARS‐CoV‐2 vaccine‐related dermatological manifestations is still lacking. A systematic review of 229 articles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 244 publications
(449 reference statements)
0
44
0
1
Order By: Relevance
“… 3 Dermatological reactions were found to be more common after the Pfizer and Moderna vaccines. 1 Sinopharm, an inactivated virus SARS‐CoV‐2 vaccine, was developed in China. This vaccine induced mild, self‐limiting adverse reactions, most commonly pain at the injection site and fever.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 3 Dermatological reactions were found to be more common after the Pfizer and Moderna vaccines. 1 Sinopharm, an inactivated virus SARS‐CoV‐2 vaccine, was developed in China. This vaccine induced mild, self‐limiting adverse reactions, most commonly pain at the injection site and fever.…”
Section: Discussionmentioning
confidence: 99%
“…A wide spectrum of skin manifestations has occurred among coronavirus vaccine recipients, which appear to be more common with the Moderna vaccine. 1 Injection site reactions are the most common cutaneous reaction to COVID‐19 vaccines. Fixed drug reaction (FDE) is a rare skin side effect previously reported in eight cases after COVID‐19 vaccines, but none of them after the Sinopharm vaccine.…”
Section: Introductionmentioning
confidence: 99%
“… 9 Moreover, vaccine studies reported that cutaneous lesion occurred after COVID‐19 vaccine inoculation, especially among children. 10 It is biologically plausible that the identified ACC in this newborn resulted from his immunological responses to the maternal SARS‐CoV‐2 infection, which impacts the fetus in utero and cause damage to the fetal skin development.…”
Section: Figurementioning
confidence: 99%
“…Covishield and other SARS-Cov-2 vaccines may also lead to cutaneous reactions, mainly at local sites, and delayed large local reactions. Urticaria, vasculopathic manifestations, pityriasis rosea-like eruptions, and herpes zoster have also been associated with Covishield and other SARS-Cov-2 vaccines 4 )-( 5 . We report a case of facial angioedema that followed the first dose of Covishield.…”
Section: Introductionmentioning
confidence: 99%